Tarum Areuy untuk Materi Ajar Teks Budaya Sunda Berbasis Quizizz Kurikulum Merdeka di SMPN 1 Ciawi Tasikmalaya - Moch. Fharaz Aulia Akbar; Retty Isnendes; Ade Sutisna (Badan Riset dan Inovasi Nasional (BRIN), 2024)
Tarum Areuy is a plant of local wisdom from Sundanese culture, this plant can be used as teaching material for learning Sundanese. Based on the following information, this research aims to describe Tarum Areuy and its functions and apply the research results to be used as teaching material for Sundanese cultural texts located at Ciawi Tasikmalaya 1 State Junior High School using the concept of an independent curriculum. The research method used uses a qualitative descriptive method with observation techniques, interviews, evaluation and documentation tools, as well as using data processing analysis. The description of Tarum Areuy in this research includes the name, past history, current history, and knowledge from the local community. The function of Tarum areuy in this research includes the use of indigo substances in dyes, making jumputan batik, and quizizz-based learning media, apart from that it has functions in economic, educational, fertilizer, medical and collection aspects. The results of research regarding the description and function of Tarum Areuy made teaching materials for Sundanese cultural texts using the Systemic Functional Linguistic-Genre Based Approach technique at State Junior High School 1 Ciawi using phase D competencies in the local content of the independent curriculum, after which students were given procedures for making jumputan batik then practice it in class, then students fill in quizizz questions that are in accordance with basic competencies, question indicators, and cognitive level according to the needs of the independent curriculum, then given an evaluation tool after learning is complete. In general, the Tarum Areuy object in this research is a learning background in introducing local Sundanese cultural wisdom which can be considered by the school, because descriptions, functions and learning can be conveyed through theory, practice and evaluation tools along with the presentation results according to the needs of the independent curriculum in schools.